A critical review of BIM adoption in public infrastructure projects: global trends and lessons for South Africa - Mashinini, Peter China; Mahachi, Jeffrey; Gumbo, Trynos; Mphambukeli, Thulisile Ncamsile (Frontiers in Built Environment, 2025)
PurposeThis review interrogates global Building Information Modelling (BIM) uptake in public-infrastructure programmes to distil evidence-based lessons and policy levers relevant to South Africa’s Public–Private Partnership (PPP) pipeline.FindingsStatutory mandates aligned to ISO 19650, ministerial steering bodies and open-standard deliverables consistently accelerate BIM diffusion and generate cost-accuracy improvements of 5%–10%, carbon savings of 15%–20% and dispute reductions of up to 40%. Conversely, voluntarist policies, SME skills gaps and fragile digital infrastructure fragment value chains. South Africa exhibits all three weaknesses: only 15% of firms produce federated models, and no Treasury directive hard-codes IFC deliverables. Evidence indicates that regional BIM labs, grading-linked competence requirements and incentive-weighted procurement can close these gaps.Research limitations/implicationsThe study relies on published cases, grey literature and proprietary project data were excluded, potentially understating undocumented innovations. Future mixed-methods research on live South African PPPs is required to quantify policy impact.Practical implicationsRecommendations include amending the PPP Manual to mandate ISO 19650/IFC models, establishing a Treasury-funded Digital Infrastructure Skills Fund, and integrating BIM metrics into CIDB grading and payment schedules.Originality/valueThe paper synthesises heterogeneous global evidence into a coherent maturity framework and offers the first targeted, policy-ready road-map for BIM diffusion in South Africa’s infrastructure sector.